Pain management in community-dwelling older adults with moderate-to-severe dementia. (2nd May 2021) - Ando, Chiaki; Kanno, Yusuke; Uchida, Osamu; Nashiki, Emiko; Kosuge, Noriko; Ogawa, Asao
Abstract : Background: This study explored visiting nurses' knowledge and beliefs regarding pain management in community-dwelling older adults with moderate-to-severe dementia. Methods: A cross-sectional study design was used to collect data in 2019. A questionnaire was mailed to nursing managers at 1037 home-visiting nursing stations in Japan. Findings: The final analysis included 230 responses. The mean score on the knowledge and belief statements was 14 out of a possible 18, and respondents with more pain management training obtained a higher total score on knowledge than those without such training (p<.001). More than 95% indicated that they needed training on pain management for older adults with dementia. Conclusion: Visiting nurses in Japan require training in pain management for older adults with moderate-to-severe dementia. Despite its usefulness, the current pain management training programme should be improved to enable visiting nurses to manage dementia patients' pain more confidently.